EVALUASI IMPLEMENTASI MANAJEMEN RISIKO PADA PROSES PEMBERIAN KREDIT - RICA DELIANDRA (Fakultas Ekonomi dan Bisnis, Universitas Airlangga, 2019)
Introduction: This research evaluates the implementation of credit risk management in the Bank “X”, which is to mitigate risks. The focused is on the application of risk management components, namely the identification , measurement, control , and monitoring of credit risk. Methods: This study uses Bank